Pengaruh Kualitas Pelayanan Jasa Wedding Organizer terhadap Tingkat Kepuasan Konsumen di The Right Two Wedding Organizer Bali - Aleksandra, I Gusti Agung Ayu Mia; Arjaya, Ketut; Sumadi, I Gede (HeadWay Research & Developemnt, 2024)
This study aims to analyze the impact of service quality on customer satisfaction at The Right Two Wedding Organizer Bali. This quantitative study evaluates the effect of service quality on customer satisfaction at The Right Two Wedding Organizer. With a population of 146 consumers using the service from January 2019 to December 2023, a sample of 60 respondents was determined using the Slovin technique. The research was conducted in Denpasar, Bali, from December 2023 to June 2024. Data was collected through questionnaires, interviews, and documentation, and analyzed using validity and reliability tests, as well as simple linear regression. The results indicate that service quality has a positive and significant effect on customer satisfaction, with a t-value greater than the t-table (12.454 > 2.00100) and a significance level of 0.000 < 0.05. The coefficient of determination shows that service quality contributes 72% to customer satisfaction, with 28% influenced by other variables. The dimension of empathy received the highest score (4.628), while the dimension of physical evidence received the lowest score (4.534). These findings can help The Right Two Wedding Organizer focus on improving service aspects that significantly impact customer satisfaction.